2004
DOI: 10.1016/j.cbpc.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 in salivary glands isolated from tobacco hornworms, Manduca sexta

Abstract: We describe a phospholipase A2 (PLA2) associated with the salivary glands of tobacco hornworms, Manduca sexta. This enzyme is able to hydrolyze arachidonic acid from the sn-2 position of PLs. Addition of the calcium chelator, EGTA, or calcium, to the Tris reaction buffer impaired the PLA2 activity, from which we infer the enzyme requires very low concentrations of calcium or perhaps other ions for optimal activity. PLA2 activity was sensitive to protein concentration (highest activity at 25 μg protein per μl),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A recent study showed that a salivary lipase (MdesL1) of Mayetiola destructor was involved in extra-oral digestion and host cell permeability [41] . In another study, phospholipase A 2 in the salivary glands of Manduca sexta may have been involved in the hydrolysis of fatty acid moieties from dietary phospholipids and also in killing food-borne bacteria [42] . The functional characterization of these hydrolases and of the digestive enzymes of the BPH may shed light on this species' mode of extra-oral digestion and plant defense suppression.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that a salivary lipase (MdesL1) of Mayetiola destructor was involved in extra-oral digestion and host cell permeability [41] . In another study, phospholipase A 2 in the salivary glands of Manduca sexta may have been involved in the hydrolysis of fatty acid moieties from dietary phospholipids and also in killing food-borne bacteria [42] . The functional characterization of these hydrolases and of the digestive enzymes of the BPH may shed light on this species' mode of extra-oral digestion and plant defense suppression.…”
Section: Resultsmentioning
confidence: 99%
“…Since no ESTs characteristic of classical phospholipases have been reported from lepidopteran midgut, it is likely the phospholipase A2 activities that have been characterized from the midgut and salivary gland of Manduca sexta (Stanley et al. , 1998; Rana & Stanley, 1999; Tunaz & Stanley, 2004) are pancreatic lipases.…”
Section: Discussionmentioning
confidence: 99%
“…, 2009) and phospholipase A2 (Stanley et al. , 1998; Rana & Stanley, 1999; Tunaz & Stanley, 2004) activities from lepidopteran larval midgut, fat body and salivary gland, and lipase and phospholipase activities from Coleoptera, Diptera and Hemiptera (Uscian et al. , 1995; Nor Aliza & Stanley, 1998; Pistillo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lipases are multifunctional proteins involved in lipid acquisition, storage and mobilization besides their involvement in reproduction and development (Mamidala et al, 2011a;Horne et al, 2009). Lipases perform a diverse and unique array of functions in insects and are well documented in several blood feeding insects, however, these are poorly understood in phytophagous insects (Arrese and Soulages, 2010;Tunaz and Stanley, 2004;Anderson et al, 2006). In a recent study of Mayetiola destructor, a lipase salivary transcript (MdesL1) was shown to be involved in extra-oral digestion and host cell permeability (Anderson et al, 2006).…”
Section: Protein Domainsmentioning
confidence: 95%